Optimization and Efficacy Evaluation of NADES-Based Green Extraction for Total Flavonols from Eleutherine plicata Herb - Li, Xi; He, Ping; Guo, Jie; Kan, Xurundong; Peng, Chunying; Li, Xueling (International Journal of Agriculture and Food Sciences Research, 2026)
Flavonols in Eleutherine plicata have significant pharmacological value, but traditional extraction is inefficient and toxic. A green NADES system (3 sugars as HBDs, 2 acids as HBAs) was screened, characterized, and optimized by single-factor/orthogonal tests. Xylose-citric acid NADES performed best (16.81%, typical NADES properties). Optimized conditions: xylose/citric acid 1:4, 15% water, 1:2 solid-liquid ratio, 50℃/50 min. Validation yielded 24.42% (RSD=1.96%), far exceeding traditional methods (≈1.97%), and stable. This system solves the low-efficiency issue and provides a reference for natural flavonoid extraction.